Animal models for human herpesvirus 6 infection - Reynaud, Joséphine; Horvat, Branka (Frontiers in Microbiology, 2013)
Human herpesvirus (HHV)-6A and HHV-6B are two enveloped DNA viruses of β-herpesvirus family, infecting over 90% of the population and associated with several diseases, including exanthema subitum (for HHV-6B), multiple sclerosis and encephalitis, particularly in immunosuppressed patients. Animal models are highly important to better understand the pathogenesis of viral infections. Naturally developed neutralizing antibodies to HHV-6 or a related virus were found in different species of monkeys, suggesting their susceptibility to HHV-6 infection. Both HHV-6 DNA and infectious virus were detected in experimentally infected Cynomolgus and African green monkeys, although most animals remained clinically asymptomatic. Furthermore, HHV-6A infection was shown to accelerate the progression of AIDS (acquired immunodeficiency syndrome) in macaques and to lead to the development of neurological symptoms in the marmoset model. Humanized SCID (severe combined immunodeficiency) mice efficiently replicated HHV-6 and were also susceptible to coinfection with HHV-6 and HIV-1 (human immunodeficiency virus 1). As CD46 was identified as a receptor for HHV-6, transgenic mice expressing human CD46 may present a potentially interesting model for study certain aspects of HHV-6 infection and neuroinflammation.